STUDENTS ORDER THINKING SKILL IN LEARNING ENGLISH - Rosi Anjarwati; Ima Chusnul Chotimah; Lailatus Sa'adah (Universitas Islam Lamongan, 2019)
This research aims to know the students order thinking skill from their written answer in reading skills. By knowing their order thinking skill, it is used as basic for the teachers to design the learning process which fit to improve students higher order thinking. This research used qualitative design, content analysis, which is analyzed students answer document in reading skill. The data is the students answer in reading skill by using herringbone technique. The data shows that 18 students are in Low Order Thinking Skill (LOTS) in which in making several questions based on WH- Questions they only do the repetition and imitation from the information given, 11 students are in Middle Order Thinking Skill (MOTS) in which they are able to think in different domain, and only 1 student is in Higher Order Thinking Skill (HOTS) in which he can improve and create an idea from the information given.Key words: HOTS, Order Thinking, Reading